2019
DOI: 10.3390/genes10110944
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Regulatory Network of Leaf Premature Senescence in Maize (Zea mays L.) Using Transcriptome Analysis of ZmELS5 Mutant

Abstract: Leaf premature senescence largely determines maize (Zea mays L.) grain yield and quality. A natural recessive premature-senescence mutant was selected from the breeding population, and near-isogenic lines were constructed using Jing24 as the recurrent parent. In the near-isogenic lines, the dominant homozygous material was wild-type (WT), and the recessive material of early leaf senescence was the premature-senescence-type ZmELS5. To identify major genes and regulatory mechanisms involved in leaf senescence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…There is no exception for premature senescence in plants, such as the mechanisms of leaf color formation in an anthurium ( Anthurium andraeanum Linden cv. ‘Sonate’) mutant [ 35 ], the mechanisms of yellow leaf mutation in crape myrtle ( Lagerstroemia indica L.) [ 36 ], and the gene regulatory networks of premature leaf senescence in corn [ 37 ], rice [ 38 ], and wheat [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no exception for premature senescence in plants, such as the mechanisms of leaf color formation in an anthurium ( Anthurium andraeanum Linden cv. ‘Sonate’) mutant [ 35 ], the mechanisms of yellow leaf mutation in crape myrtle ( Lagerstroemia indica L.) [ 36 ], and the gene regulatory networks of premature leaf senescence in corn [ 37 ], rice [ 38 ], and wheat [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al's study has shown that enzymes involved in chlorophyll degradation are significantly upregulation at the later stage of plant growth and development, and chlorophyll degradation is enhanced 55 . In Chai M's study, genes involved in photosynthesisrelated and stress responses as well as the cellular components of chloroplast, PSI and photosynthetic membrane of the premature aging mutant ZmELS5 were down-regulated, consistent with chlorophyll decomposition and reduced photosynthesis 56 . The results of this study provided a theoretical basis for analyzing the growth and development of maize leaves from the perspective of histone methylation modification.…”
Section: Discussionmentioning
confidence: 93%
“…The online tool STRING V11 ( , accessed on 18 August 2022) was used to build connect network of those GO terms [ 54 ].…”
Section: Methodsmentioning
confidence: 99%